Ash Wednesday a novel - Hawke, Ethan 1970- (Knopf, 2002)
Jimmy, AWOL from the Army, heads across America from Albany to New Orleans, Ohio, and Texas in a souped-up Chevy with his pregnant girlfriend, Christy, transforming themselves from passionate lovers into a young family along the way.
Keywords: Absence without leave -- Fiction; Automobile travel -- Fiction; Love stories.; Pregnant women -- Fiction; Soldiers -- Fiction; Unmarried couples -- Fiction; Fiktionale Darstellung; Domestic fiction; Love stories